The Effectiveness of Companyâ€™s Financial Analysis and Supply Chain Policy in Predicting the Future Prices of Stocks - Ahmed Rahi Abed; Ahmed Mahdi Hadi; Ahmed Kadhim Sendw (International Journal of Supply Chain Management, 2019)
The core idea behind this research is to examine the significance of financial ratios taken from the financial reports or statements to forecast trend in stock price. For this purpose financial ratios have been taken to forecast stock returns from 2008 to 2018. Thus to predict the future price of stock four financial ratios have been taken, â€œprice to book ratio (P/B), price to earnings ratio (P/E), dividend per share (DPS) and firm sizesâ€. This research comprises on panel data with fix and random effect model for analysis that is a very effective and comprehensive predictive regression method for forecasting the stock returns. This study reveals results which show that the financial ratios are the most efficient tool for predicting stock returns. Among the four taken ratios in this research the firm size has proven to be more accurate prediction power as compare to dividend per share as well as price to book ratio. Nevertheless, the relationship between price to earnings ratio and stock returns has not been proven to be significant. Thus the study has proven that financial ratios are reliable tool to predict stock price while making investment decisions.